Public Sector Accounting as a Mechanism for Anti-Corruption and Good Governance: A Literature Review - Maulidina, Andini; Ramadhani, Nazwa; Mutmayna, Nuri; Sahya, Salfa; Ramadhani, Yasmin Nur; Saputra, Praja Hadi (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
Corruption and fraud remain the main problems in public sector governance in Indonesia, as they contribute to state financial losses, declining performance of government agencies, and weakening public trust. Weak public-sector accounting systems, internal controls, and the implementation of good governance principles often create opportunities for the abuse of authority. This Research aims to comprehensively examine the contribution of public sector accounting in preventing corruption and fraud and its role in supporting the improvement of good governance. The research method is a literature review, examining and analyzing national and international scientific journals relevant to public sector accounting, good governance, internal supervision, auditing, and the use of technology in public financial management. The results of the study show that implementing transparent and accountable public-sector accounting significantly improves government agency performance and reduces corruption and fraud. Strengthening the principles of good governance and the effectiveness of internal supervision has been proven to enhance the accounting function as an instrument of public control and accountability. In addition, adopting accrual-based accounting and international standards, such as the International Public Sector Accounting Standards (IPSAS), can improve the quality of financial information and reduce information asymmetry. However, the effectiveness of its implementation depends heavily on institutional support, the quality of the legal system, political stability, and anti-corruption commitments. Therefore, preventing corruption in the public sector requires an integrated approach that combines strengthening public sector accounting, good governance, internal supervision, independent audit, and sustainable use of technology.